Pencabulan terhadap Anak dalam Tinjauan Hukum Pidana Islam dan Undang-Undang Nomor 35 Tahun 2014 (Studi Kasus di Desa Manambin Kecamatan Kotanopan): Child Abuse in Review of Islamic Criminal Law and Law Number 35 of 2014 (Case Study in Manambin Village, Kotanopan District) - Khorun Nisa; Ramadani, Ramadani (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2024)
This study aims to investigate the perspective of Islamic criminal law and Law No. 35 of 2014 on cases of violence against children in Manambin Village, Kotanopan Regency. This study uses empirical law and case study methodology. We engage in direct communication with those working in the field to ascertain the source of the problem. The results of this study indicate that ta'zir is the right punishment for those who commit acts of violence against children. A fine of up to five million rupiah and a prison sentence of five to fifteen years are the penalties for violating the rules and laws relating to child protection. The findings of this study are expected to inform community norms in responding to child abuse and neglect.